2020
DOI: 10.1186/s12917-020-02282-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of Peptiva, a peptide-based feed additive, can accelerate the maturation of the fecal bacterial microbiome in weaned pigs

Abstract: Background: Weaning is one of the most critical transition stages of the swine production cycle, as the piglet gut physiology and microbiome need to rapidly adapt to changes in diet and environmental conditions. Based on their potential for producing a vast array of bioactive molecules, peptide formulations represent a largely untapped source of compounds that could be developed into feed additives to benefit animal health and nutrition. In this context, a commercial-scale nursery trial was performed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 60 publications
6
15
0
Order By: Relevance
“…Ssd-00001, which was closely related to L. amylovorus, showed fluctuations in abundance across time points, with its highest abundance observed during the transition from phase II to phase III diets. The timing of these changes is consistent with previous studies [32,45], highlighting the impact of diet on modulating gut bacterial composition. L. amylovorus has shown potential probiotic properties, including antimicrobial activity against enteric pathogens and maintaining a healthy gut microbiome [46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ssd-00001, which was closely related to L. amylovorus, showed fluctuations in abundance across time points, with its highest abundance observed during the transition from phase II to phase III diets. The timing of these changes is consistent with previous studies [32,45], highlighting the impact of diet on modulating gut bacterial composition. L. amylovorus has shown potential probiotic properties, including antimicrobial activity against enteric pathogens and maintaining a healthy gut microbiome [46].…”
Section: Discussionsupporting
confidence: 90%
“…Observed taxonomic profiles were consistent with previous research studies, as the two most dominant phyla in weaned pig fecal microbiota were Firmicutes and Bacteroidetes [30][31][32]. While the abundance of major phyla did not vary between treatment groups at any given time point, differences were noted at the family and OTU levels, which may indicate gut microbiota modulation due to treatment with phytobiotics.…”
Section: Discussionsupporting
confidence: 89%
“…Raw bacterial 16S rRNA gene V1–V3 amplicon sequences were provided by Molecular Research DNA (MRDNA, Shallowater, TX, USA) as assembled contigs from overlapping MiSeq (2 × 300) paired-end reads from the same flow cell clusters. Reads were then selected to meet the following criteria: the presence of both intact 27F (forward) and 519R (reverse) primer nucleotide sequences, a length between 400 and 580 nt, and a minimum quality threshold of no more than 1% of nucleotides with a Phred quality score lower than 15 [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following quality screens, sequence reads were aligned, then clustered into Operational Taxonomic Units (OTUs) at a genetic distance cutoff of 5% sequence dissimilarity [ 49 , 50 ]. OTUs were screened for DNA sequence artifacts using the following methods.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al also reported that cecropin AD enriched Lactobacillus and reduced diarrhea incidence in weaned piglets challenged with E. coli [ 153 ]. In addition, Poudel et al found that a peptide-based additive could accelerate the maturation of swine gut microbiota [ 154 ].…”
Section: The Effects Of Nutritional Interventions On Swine Gut Health Around Weaningmentioning
confidence: 99%